SISTEMUL CARSTIC – ASPECTE TEORETICE (PANGEEA, 2025)
ABSTRACT. Karst system - theoretical aspects. In our days, the reality is more and more regarded as a whole, as a system, with plenty of self-organised subsystems that are hierarchically organised. So is the karst system – a geomorphological system that has specific structure and functionality, having a sinergical effect through its functionality. In the last decades, some researchers of karst began to develop models of karst systems structure and functionality. In our work, we tried to understand the structure and functionality of karst system through its specific morphological forms: the exokarstical and the endokarstical forms, that are interrelated, especially in the mature phase of karst evolution, like the karst of Pădurea Craiului Mountains, Romania. These karst forms and their atributes can be regarded as morphological responses of karst system toward the impact of disturbing forces of the control factors that are working in the karst environment, being the expressions of sensitivity levels in the systems. In that approach, we may get closer in our researches to the model of „grey box” , instead of the „black box” model, at least morphologically. In that way, these informations could be used even by the speologists who are working in the field. Key words: karst system, self-organisation, hierarchy, sinergy, exokarst, endokarst, interrelations, morphological response, disturbing force, control factor, sensitivity, „black box”, „grey box”.